The quest for unity between the Bantu Presbyterian Church of South Africa and the Presbyterian Church of Southern Africa, 1959-1973 - Xapile, Spiwo Patrick (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2000.